A importância do programa formando cidadão para a redução dos atos infracionais e para o fortalecimento da cultura da não violência - Chagas, Suzy Dayana Pereira (2018)
This research proposes as a theme of study "The importance of social programs for the reduction of infractions". Thus, the general objective of the research is to evaluate the effectiveness of the Forming Citizen Program, bases located in the city of Manaus, regarding the decrease in the commission of infractions, as well as massification of the culture of nonviolence. Among the specific objectives are: to raise the evasion rates of the Forming Citizen Program participants, to describe the perception of the members of the Forming Citizen Program, to discuss if the actions developed in the Forming Citizen Program have led participating adolescents to critically reflect the consequences of violence committed and suffered, and finally, propose a model of evaluation to measure the results achieved by the Program Training Citizens with respect to prevention and strengthening of the culture of nonviolence. The method used to develop the research was the bibliographical survey, the field research and the documentary research, having as subjects of the field research, program managers and the minor participants of the Forming Citizen Program. The results pointed to the achievement of the desired effectiveness with the implementation of the program, specifically with regard to the prevention and strengthening of a culture of peace (culture of non-violence).